Video-mediated rural learning: effects of images and languages on farmers' learning in Benin Republic. Issue 1 (2nd January 2021) - Bede, Lauréano; Okry, Florent; Vodouhe, Simplice D.
ABSTRACT: Training videos are extension tools that help to compensate for the low ratio of extensionists to farmers in most developing countries. This article reports on a study that aimed to understand the effects of images and languages used in a video on farmers' learning. The research involved 135 rice farmers in Benin Republic, and found that videos in the local language significantly improved assimilation and understanding. Repeated screenings increase farmers' learning, regardless of the language used, as videos allow learning from images. Farmers' associations and peer groups ensure better appropriation and dissemination of the knowledge gained from the videos by providing frameworks for discussion.